Students’ Language Production in Duolingo-Based Learning: A Qualitative Study in Mobile-Assisted Language Learning Context - Rendi Nurhidayat; Lusiana Suciati Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Second language learning is a complex process involving cognitive, linguistic, and social dimensions, particularly within the framework of Second Language Teaching (SLT), which emphasizes a balance between linguistic accuracy and communicative language use. In recent years, mobile-assisted language learning (MALL) has significantly influenced learning practices by enabling flexible access to materials beyond the classroom and increasing learners’ exposure to the target language. One widely used application in this context is Duolingo, which provides structured, pattern-based exercises to improve vocabulary and grammatical accuracy. However, previous studies have primarily focused on learning outcomes, with limited attention to how learners produce language after engaging with such exercises. This study aims to analyze students’ language production abilities following their interaction with Duolingo. It employed a descriptive qualitative approach with a process-oriented classroom observation design involving two junior high school students learning English as a foreign language. Data were collected through observation checklists, field notes, and students’ language output during and after learning sessions, focusing on grammar, vocabulary, fluency, pronunciation, and coherence. The findings indicate that students were able to produce simple and understandable sentences however, their production remained limited and predominantly reproductive, as reflected in grammatical inaccuracies, restricted vocabulary, and reliance on patterns. Although fluency and pronunciation were relatively adequate in familiar contexts, both participants showed limitations in producing varied and coherent sentences independently, highlighting the need to integrate communicative activities.